The WHO-5 Well-Being Index: A Validation Study in People with Infertility - Reza OMANI-SAMANI; Saman MAROUFIZADEH; Amir ALMASI-HASHIANI; Mahdi SEPIDARKISH; Payam AMINI (Tehran University of Medical Sciences, 2019)
Background: Infertility is a public health problem and can lead to depressive symptoms. In recent years, the WHO-five Well-being Index (WHO-5) has been used as a screening measure for depression, but study on psychometric properties in people with infertility is scarce. The objective of this study was to examine the reliability and validity of the Persian version of the WHO-5 in people with infertility. Methods: Overall, 539 infertile patients from a referral infertility center in Tehran, Iran in the period between May and Aug 2017, completed the WHO-5, along with other psychological measures: the Patient Health Questionnaire-9 (PHQ-9) and the Hospital Anxiety and Depression Scale (HADS). Construct validity and internal consistency of WHO-5 were evaluated using confirmatory factor analysis (CFA) and Cronbach's alpha, respectively. Convergent validity was examined by relationship with PHQ-9 and HADS. Results: The prevalence of poor well-being was 44.3% and that of depression was 18.6%. CFA confirmed the unidimensional factor structure of the WHO-5. Internal consistency of the WHO-5 was good (Cronbach's alpha=0.858). The WHO-5 significantly correlated with the PHQ-9 (r=-0.522), HADS-anxiety (r=-0.524) and HADS-depression (r=-0.630), confirming convergent validity. Conclusion: The WHO-5 is a short and easy to use questionnaire with satisfactory reliability and validity that appears suitable for use as a screening test for depressive symptom in infertile people. In addition, the prevalence of depression and poor well-being was very high in this population.